Eksplorasi Kandungan Gizi Ikan Sibero (Hampala macrolepidota) Sebagai Bahan Baku Dalam Pembuatan Produk Pangan Perikanan - Ahmad Fauzan Lubis; Andri Syaputra (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
Sibero fish (Hampala macrolepidota) is a freshwater fish caught by fishermen in the glare river area of Tanjungbalai City. However the number of fish catches is inversely proportional to the sales results. Sibero fish is not a favorite fish for consumption because sibero fish have many bones making it difficult to consume. However, this special processing of sibero fish can become a raw material that is of public interest because sibero fish meat has good nutritional value and tastes good. The purpose of this study was to determine the nutritional content of sibero fish through chemical compositions which include proximate to the proportion of body parts, and increase the potential of sibero fish as food products that have added value through information from the nutritional content. The research method used is the experiment method. The parameter observed was a proximate analysis of the proportion of sibero fish body parts. The results of the study are sibero fish based on the proportion of sibero fish body parts divided into three parts, namely (1) Caput / head section, (2) Truncus / body part, and (3) Cauda / tail section. Comparison of the chemical composition of the proportion of body parts to the content of water content obtained the highest value in the truncus (64.19%) and the lowest value in the head (57.11%). The highest ash content in the caput (2.37%) and the lowest in the cauda (1.90%). The highest protein in the caput (18.66%) and the lowest in the cauda (14.42%). The highest fat content in the caput (21.66%) and the lowest was in cauda (11.87%). The highest carbohydrate value in the cauda section (8.85%) and the lowest value in the caput section (0.20%).